al-tanqīb fī Tall al-Ḍubā‘i: al-mawsim al-ṯāliṯ, 1984 - Šākir, Muḥammad Maḥmūd
Excavation at Tell al-Dhuba‘i: Third Season, 1984; ersch. 1987; including three (two cylinder and one flat egg-shaped) seals and a mold for making pendants; including three (two cylinder and one flat egg-shaped) seals and a mold for making pendants.